What social media can tell us about essential occupations : contextualising twitter data to understand shifts in occupational valuations - Tiemann, Michael [Verfasser]; Udelhofen, Stefan [Verfasser]; Fournier, Lisa [Verfasser] (Gesellschaft für Informatik e.V.., 2023)
"Societal debates about essential occupations in the context of the pandemic have raised questions about the valuation of occupational tasks. In a first step we compare two lists of essential occupations, one from the start, the other from the end of the pandemic, to describe differences in their valuation based on characteristics such as wages, prestige and workload. Between these lists it becomes apparent that there has been a broadening shift, with essential occupations at the end of the pandemic being different to what they were at the beginning. This is based on data from the BIBB/BAuA Employment Survey 2018. We then investigate the use of twitter data for generating insights on how the valuation of occupations were discussed and changed during the pandemic and thus helped leverage said shift in essential occupations." (Authors' abstract, BIBB-Doku)
Keywords: 370; Systemrelevanter Beruf; Pandemie; BIBB/BAuA-Erwerbstätigenbefragung; Social Media; Wertschätzung; Sozialprestige; Qualifikationsniveau; Lohn